Supporting the prevention conversation: a developmental evaluation of an innovative FASD awareness and prevention initiative - Dayal, Helena (My University, 2015)
This document presents findings from the developmental evaluation of this initiative, the purpose of which was to provide key information to stakeholders in order to inform their future decisionmaking regarding this FASD prevention initiative. The evaluation also served to track the development and implementation of the initiative, in order to assess its transferability to new contexts. This developmental evaluation employed a mixed-methods approach, collecting data from Facilitators, Service Providers, and key project team members to answer four key evaluation questions. Data collection took place between May 2013 and January 2015, during the period of development and the first year of the implementation (2014) of the initiative.